2020
DOI: 10.31925/farmacia.2020.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cetuximab/Panitumumab After Previous Bevacizumab in Metastatic Colorectal Cancer

Abstract: The optimal sequence of the targeted therapies in metastatic colorectal cancer is not established. We aimed to analyse if previous administration of bevacizumab impacts the response to epidermal growth factor receptor inhibitors in subsequent lines of therapy. It was performed a retrospective analysis on KRAS or KRAS/NRAS wild-type metastatic colorectal cancer patients that received an epidermal growth factor receptor inhibitor in the second or later lines of therapy and their outcom es were analysed according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This study demonstrated that AL3818 could reduce the expression of TLR-4, NF-κB, VEGF and survivin while increasing the expression of Bax in a dose-dependent manner. The VEGF family can stimulate angiogenesis in neoplastic tissues, allowing tumour cell proliferation and metastatic spread [29,30]. Therefore, our data further supported the apoptosisinducing effects of AL3818, which may be a key strategy for preventing tumour recurrence and metastasis.…”
Section: Protein Expression Profiles By Western Blotsupporting
confidence: 77%
“…This study demonstrated that AL3818 could reduce the expression of TLR-4, NF-κB, VEGF and survivin while increasing the expression of Bax in a dose-dependent manner. The VEGF family can stimulate angiogenesis in neoplastic tissues, allowing tumour cell proliferation and metastatic spread [29,30]. Therefore, our data further supported the apoptosisinducing effects of AL3818, which may be a key strategy for preventing tumour recurrence and metastasis.…”
Section: Protein Expression Profiles By Western Blotsupporting
confidence: 77%
“…Furthermore, in vitro studies revealed that the stimulation of gingival fibroblasts with CsA for 24 h caused a significant decrease in the apoptosis rate through both the intrinsic and extrinsic pathways, mitochondria and ER playing an important role in this process [10]. We acknowledge that the early important events in apoptosis take place at the mitochondrial and ER level by cytochrome c and calcium release in the cytoplasm [11,12]. The ER is the site for synthesis, folding, modification and trafficking of secretory and cell-surface proteins.…”
Section: Introductionmentioning
confidence: 98%
“…VEGF is considered a highly important target of anticancer therapy, being one of the main proteins expressed by tumour cells [31]. Oncology drugs that inhibit the growth of VEGF are increasingly being employed in the clinic [4,16,21,22,24,25,36,51]. Previous economic reviews of bevacizumab in patients with mCRC in the United States of America, the United Kingdom, Canada, Australia and Israel indicated a lack of cost-effectiveness [9,18,19], rGBM in Canada [28], mCC in the USA [46], and ovarian cancer in Canada and Belgium [3,35] and a systematic evaluation including ten countries reported that the costeffectiveness of bevacizumab in NSCLC was inconclusive [29].…”
Section: Direct Costs On Monthsmentioning
confidence: 99%